Answer:
Ok, i will answer in English.
The first step is to know that when we have a linear equation like:
y = a*x + b
any line with a slope equal to -1/a will be perpendicular to our line.
So first let's write our equation in the standard form:
4x + 6y - 6 = 0
6y = -4x + 6
y = (-2/3)*x + 1
then the slope is (-2/3)
then the slope of the perpendicular line will be:
-(1/(-2/3)) = 3/2
So the only thing any line with the equation:
y = (3/2)*x + c
where c can be any real number, is perpendicular to 4x+6y-6=0